The First-stage Analysis on the Results of Mass Screening for Colororectal Cancer - Ishizawa, T.; Nuruki, K.; Makisumi, K.; Shimazu, H.; Makisumi, S.; Imakiire, S. (Nippon Daicho Komonbyo Gakkai Zasshi, 1992)
Recently, much attention has been paid to mass sceening aiming at early detection and early treatment of colorectal cancer in Japan. From April 1990, we also began mass screening using a one-day method fecal occult blood test with RPHA and questionaire concerning the complaints of the patients. The present article analyzes the results of the screening conducted during the first year. A total of 4, 930 inhabitants in Makurazaki and Bhonotsu areas in Kagoshima Prefecture were examined, and 3, 536 of them (71.7%) were subjected to the analysis. One thousand and seventy-three subjects (30.3 %) were assessed positive for cancer. Four hundred and seven of them (37.9%) underwent detailed examinations such as digital examination, sigmoidoscopy and barium meal enema. Colorectal cancer was found in 9 cases, which corresponded to 0.3% of the subjects having undergone initial examinations. In 5 of them, fecal occult blood test was positive, but the other 4 subjects had been checked by questionaire indicating the importance of a combination of the two screening methods as far as the first-stage analysis, was concerned